Synthesis and Characterization of Cinnamon Bar Soap from Waste and New Cooking Oils: A Comparative Study - Mohd Nur Izzuddin Rosman,; Siti Aida Ibrahim,; Ainuddin, Ainun Rahmahwati; Niki Prastomo, (International Journal of Integrated Engineering, 2025)
Improper disposal of waste cooking oil led to environmental risks. Converting waste cooking oil into handmade soap, especially by adding cinnamon, offers a sustainable reuse method. This study investigates cinnamon’s impact on soap’s cleaning ability by using cold process method. The fundamental materials used in this process such cooking oil, sodium hydroxide (NaOH), distilled water, and cinnamon. Cinnamon was added with variation concentration from 0g, 3g, 6g, 9g, and 12g for both using new cooking oil (NCO) and waste cooking oil (WCO). Soaps were evaluated for colour, pH value, FTIR analysis, moisture content, swelling test, and stain removal test. The results indicate that the soap sample from new and waste oil without cinnamon appeared nearly white, while soap samples with highest concentration of cinnamon were dark brown. Both soap from new and waste oil had a pH level of 8 and a moisture content of 11.11%. Cinnamon bar soap using new oil and 6 grams of cinnamon has the highest degradation rate at 12.31%, and cinnamon bar soap using waste oil and 3 grams of cinnamon has the lowest at 6.46%. The soap in vinegar solution showed the most chemical reaction with a pH level of 2, while the soap observed remain stable in the salt solution due to its pH value of 9. Both bar soaps from NCO and WCO are equally effective at removing stains. Specifically, both soap from new and waste oil removed 94% of soy sauce stains. For chili sauce stains, the soap using new oil removed 87%, while the soap using waste oil removed 88%. However, for lipstick stains, both soaps only managed to remove 80% of the stain. This study suggested that bar soaps made from WCO with cinnamon additives can be used as raw material in production of high-quality soap which promotes environmental responsibility and contributes to sustainable waste management.